2014
DOI: 10.1111/bjh.12732
|View full text |Cite
|
Sign up to set email alerts
|

CD137 ligand signalling induces differentiation of primary acute myeloid leukaemia cells

Abstract: SummaryCD137 ligand (CD137L), a member of the tumour necrosis factor family, is expressed as a cell surface molecule. Engagement of CD137L on haematopoietic progenitor cells induces monocytic differentiation, and in peripheral monocytes CD137L signalling promotes differentiation to mature dendritic cells. We hypothesized that CD137L signalling would also induce differentiation in transformed myeloid cells. Here we show that recombinant CD137 protein, which crosslinks CD137L and initiates reverse CD137L signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
5
2
Order By: Relevance
“…In previous studies, we revealed that the release of so4-1BBL from AML-blast samples leads to a higher plasma level and expression correlated with prognostically adverse AML subtypes what might be explained by a binding of so4-1BBL to T-cells, thereby inhibiting T-cell-c4-1BB binding to tumor cells. Moreover, c4-1BBL is known to be expressed on AML blasts’ surface8 and was stated to have an impact in the blasts’ maturation processes due to its reverse signaling capability when stimulated as shown in 15 of 21 not closer specified AML samples in a study of Cheng et al 30 that could not be confirmed in our study, probably due to a different composition of our pt cohort. In cut-off analyses, we correlated significantly higher 4-1BBL expression with shorter (but not significant) DFS and OS times, thereby providing evidence of correlation not only of a higher so4-1BBL release but also of a higher c4-1BBL expression in the case of unfavorable prognosis.…”
Section: Discussioncontrasting
confidence: 66%
“…In previous studies, we revealed that the release of so4-1BBL from AML-blast samples leads to a higher plasma level and expression correlated with prognostically adverse AML subtypes what might be explained by a binding of so4-1BBL to T-cells, thereby inhibiting T-cell-c4-1BB binding to tumor cells. Moreover, c4-1BBL is known to be expressed on AML blasts’ surface8 and was stated to have an impact in the blasts’ maturation processes due to its reverse signaling capability when stimulated as shown in 15 of 21 not closer specified AML samples in a study of Cheng et al 30 that could not be confirmed in our study, probably due to a different composition of our pt cohort. In cut-off analyses, we correlated significantly higher 4-1BBL expression with shorter (but not significant) DFS and OS times, thereby providing evidence of correlation not only of a higher so4-1BBL release but also of a higher c4-1BBL expression in the case of unfavorable prognosis.…”
Section: Discussioncontrasting
confidence: 66%
“…56 Another study demonstrated reverse CD137L signaling into AML cells induces differentiation, resulting in reduced proliferation, and suggested this approach to be explored as a novel differentiation therapy for AML. 57 In summary, the data from the role of CD137 and CD137L in cancer further support the notion of CD137-CD137L interaction promoting type 1, cell-mediated immune responses.…”
Section: Reverse Cd137 Ligand Signaling In Apc Strengthens Type 1 Cementioning
confidence: 53%
“…Recombinant TNFRSF9 protein was found to crosslink with TNFSF9 on acute myeloid leukaemia cells. It induces reverse TNFSF9 signaling, resulted in the differentiation of primary acute myeloid leukemia cells . Recently, several studies have investigated the expression of TNFSF9 on solid tumors and found that it was indeed downregulated in various tumor cell lines, including colorectal cancer, multiple myeloma, lung cancer and breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…It induces reverse TNFSF9 signaling, resulted in the differentiation of primary acute myeloid leukemia cells. 36 Recently, several studies have investigated the expression of TNFSF9 on solid tumors and found that it was indeed downregulated in various tumor cell lines, including colorectal cancer, multiple myeloma, lung cancer and breast cancer. 11,12,37,38 In lung cancer, TNFSF9 expression was positively correlated with welldifferentiated tumors, an early TNM stage and better survival.…”
Section: Discussionmentioning
confidence: 99%